2010
DOI: 10.1007/s12272-010-0812-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel itraconazole-loaded solid dispersion without crystalline change with improved bioavailability

Abstract: To develop a novel itraconazole-loaded solid dispersion without crystalline change with improved bioavailability, various itraconazole-loaded solid dispersions were prepared with water, polyvinylpyrroline, poloxamer and citric acid. The effect of carriers on aqueous solubility of itraconazole was investigated. Their physicochemical properties were investigated using SEM, DSC, and powder X-ray diffraction. The dissolution, bioavailability in rats and stability of solid dispersions were evaluated. Unlike convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…8 indicated that SM-SD exhibited faster drug release than the other preparations tested. As previously reported, rapid hydration of hydrophilic polymers promotes the drug wetting process in aqueous surroundings and enlarges the surface area of the solidewater interface, which may contribute to the improved SD dissolution rate [25]. However, SM-SD-SEDS showed a cumulative release of more than 90% in the first 5 min, whereas less than 70% release was observed from SM-SD-SE at 5 min.…”
Section: In Vitro Dissolution Testmentioning
confidence: 56%
“…8 indicated that SM-SD exhibited faster drug release than the other preparations tested. As previously reported, rapid hydration of hydrophilic polymers promotes the drug wetting process in aqueous surroundings and enlarges the surface area of the solidewater interface, which may contribute to the improved SD dissolution rate [25]. However, SM-SD-SEDS showed a cumulative release of more than 90% in the first 5 min, whereas less than 70% release was observed from SM-SD-SE at 5 min.…”
Section: In Vitro Dissolution Testmentioning
confidence: 56%
“… 10 , 13 To reinforce the dissolution rate or the physical stability of dispersed drug entities in the carrier matrix, additives such as surfactants or pH modulators can also be used. 8 , 14 , 15 It was reported earlier that the oral bioavailability of ITZ could be enhanced by coadministration with a vitamin C beverage in healthy participants. 16 Vitamin C (L-ascorbic acid, LAA), a highly acidic material, is an essential micronutrient involved in many biological and biochemical functions ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been used to improve the solubility of poorly water-soluble drugs, including using surfactants, 5 inclusion complexation, 6 , 7 and solid dispersion (SD) techniques. 8 For example, the SD technique has been well used to enhance the dissolution rate of ITZ, 4 , 8 10 and one of the commercial products of ITZ (Sporanox ® ) is a hard capsule form containing ITZ coated on sugar spheres. Drug was layered onto the sugar pellets by the fluid bed-based SD technique using hydroxypropyl methylcellulose (HPMC) as the hydrophilic dispersing material.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mosapride dispersed in carriers may achieve the highest levels of particle size reduction and surface area enhancement [26][27][28] .…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%